2017
DOI: 10.20944/preprints201709.0166.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alzheimer's Disease, Brain Injury, and C.N.S. Nanotherapy in Humans: Sonoporation Augmenting Drug Targeting

Abstract: Owing to the complexity of neurodegenerative diseases, multiple cellular types need to be targeted simultaneously in order for a given therapy to demonstrate any major effectiveness. Ultrasound-sensitive coated microbubbles (in a targeted nanoemulsion) are available. Versatile small-molecule drug(s) targeting multiple pathways of Alzheimer's disease pathogenesis are known. By incorporating such drug(s) into the targeted LCM/ND lipid nanoemulsion type, one obtains a multitasking combination therapeutic for tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…It has been reported repeatedly that endothelial modulation and repair is feasible by pharmacological targeting [1,2,[4][5][6][7][8][9][10] of the SR-BI receptors (i.e., "scavenger receptor class B, type I") [10]. As the detailed review by Mahringer et al [11] points out, the blood-brain barrier (BBB) is equipped with several endocytic receptors at the luminal surface (i.e., the capillary endothelial membrane), including SR-BI.…”
Section: Endothelial Dysfunction and Targeted Treatment For Early Dementioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported repeatedly that endothelial modulation and repair is feasible by pharmacological targeting [1,2,[4][5][6][7][8][9][10] of the SR-BI receptors (i.e., "scavenger receptor class B, type I") [10]. As the detailed review by Mahringer et al [11] points out, the blood-brain barrier (BBB) is equipped with several endocytic receptors at the luminal surface (i.e., the capillary endothelial membrane), including SR-BI.…”
Section: Endothelial Dysfunction and Targeted Treatment For Early Dementioning
confidence: 99%
“…Recently, Fung et al [12] specifically found that SR-BI mediates the uptake and transcytosis of high-density lipoproteins (HDL) across brain microvascular endothelial cells (i.e., across the BBB). Since SR-BI has already been identified as a major receptor for HDL (with their major apolipoprotein (apo)A-I), as well as for the recently reviewed [1,2] "lipid-coated microbubble/nanoparticle-derived" (LCM/ND) nanoemulsion (see below), this multitasking lipid nanoemulsion can arguably serve as a targeted, apoA-I-based, (SR-BI mediated) therapeutic agent for common (late-onset) dementias [13][14][15].…”
Section: Endothelial Dysfunction and Targeted Treatment For Early Dementioning
confidence: 99%
See 3 more Smart Citations